Podpora prodeje a reklama konkrétní společnosti - Fixová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Bakalářská práce se zaměřuje na podporu prodeje a reklamy konkrétní společnosti, která podniká v oblasti výroby, obchodu a služeb. Cílem této práce je navrhnout vhodné nástroje podpory prodeje a reklamy. Na základě provedených dílčích analýz jsou navrženy možnosti ke zlepšení. Tato doporučení jsou vhodná ke zlepšení podpory prodeje a reklamy, které povedou k navýšení počtu nových zákazníků, uspokojení jejich potřeb a tržeb analyzované společnosti.

The bachelor's thesis focuses on the sales promotion and advertising of a particular company, that operates in the field of production, trade and services. The main goal of this work is to design suitable tools for sales promotion and advertising. Based on the implementation of aprtial analyzes, the possibilities of improvement are suggested. The proposed recommendations are suitable for improving sales promotion and advertising, which will lead to an increase in the number of the new customers, satisfied their needs and sales of the analyzed company.
Sales Promotion and Advertising of Company
Keywords: Marketing; podpora prodeje; reklama; marketingový mix; komunikační mix; móda; propagace; Marketing; sales promotion; advertising; marketing mix; communication mix; fashion; promotion